You need to open the brackets:

x - 1 + ix - i + y + 1 - iy - i = 1 - 3i

You need to rearrange the terms from the left side such that:

(x - 1 + y + 1) + i(x - 1 - y - 1) = 1 - 3i

Reducing the opposite terms inside the brackets yields:

x + y + i(x - y - 2) = 1 - 3i

Equating real parts yields:

x + y = 1

Equating imaginary parts yields:

x - y - 2 = -3 => x - y = -3+2 => x - y = -1

Adding the first equation to the second yields:

x + y + x - y = 1 - 1 => 2x = 0 => x = 0 => y = 1

**The solution to the given identity is x = 0 ; y = 1.**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now